Debt Policy and Independent Commissioners’ Effects on Indonesian State-Owned Enterprises Performance: Moderation Role of Firm Size - Firmansyah, Firmansyah (JAFFA, 2026)
This study examines how debt policies and independent commissioners impact the performance of state-owned enterprises listed on the IDX over the 2019-2021 period, with company size serving as a moderating variable. Regression results from a quantitative approach and purposive sampling of 246 samples indicated that debt policies and independent commissioners had a partially positive effect on performance, and company size enhanced this relationship. Implicitly, the use of measurable debt serves as a financial discipline tool to spur asset productivity, while the role of independent commissioners ensures stronger supervisory objectivity to improve operational efficiency. Therefore, SOE management is advised to optimize the capital structure and strengthen the board’s supervisory function professionally, while the government needs to consider the scale of the company’s assets in formulating governance policies to ensure the sustainability of large-scale SOEs’ performance in the capital market.